Internal and external moisture transport resistance during non-stationary adsorption of moisture into wood - Bučar, Bojan (Zbornik gozdarstva in lesarstva, 2007)
The assumption that non-stationary sorption processes associated with wood canbe evaluated by analysis of their transient system response to the disturbance developed is undoubtedly correct. In general it is, in fact, possible to obtain by time analysis of the transient phenomenon - involving the transition into an arbitrary new state of equilibrium - all data required for a credible evaluation of the observed system. Evaluation of moisture movement during drying or moistening requires determination of external moisture transfer resistance from or to wood surfaces, as well as internal resistance. Time-dependent changes in the moisture content of the spruce (Picea abies Karst.) samples of different thickness were monitored gravimetrically, during which the frequency of weighing was in accord with thespeed of moistening. It was assumed that quasi-isothermal sorption processes associated with wood could be evaluated as first order systems. The characteristic time constant ? determines, wholly and uniformly, the time dependence of the sorption process for the relevant sorption range of wood tissue. The connection between the time constant and the thickness of the sample measured in the direction of the material flux is potential, with the power depending solely on the relationship between the external mass transfer convection and internal diffusion resistance. To determine the said resistances or coefficients of mass transfer convection and diffusivity, the experiment must be carried out on samples of varying thickness. It is only in this way that the external mass transfer convection and internal diffusion resistance can be correctly distinguished.
Keywords: adsorpcija; difuzivnost; les; masna prestopnost; prenos snovi